Mechanical and physical properties of fly ash foamed concrete - M. Gelim, Khalid. Ali. (2011)
Foamed concrete has become most commercial material in construction industry. Fly ash is receiving more attention now since their uses generally improve the properties of blended cement concrete, cost saving and reduction of negative environmental affects. The physical and mechanical properties of foamed concrete differ according to a different type of mixture and its composition. Therefore, this research investigates physical and mechanical properties of fly ash foamed concrete. Fly ash was used as fine aggregate. Six series of fly ash foamed concrete for target densities (1000, 1100,1200,1300,1400 and 1500 kg/m ) with constant cement to fly ash ratio (1:1.5) and cement to water ratio (1:0.65) by weight were prepared and tested. Tests were conducted to study physical properties (work ability, water absorption, drying shrinkage and carbonation) and mechanical strengths properties (compressive, splitting tensile and flexural strengths). Three types of specimens (cube, cylinder and prism) were used in different quantity and different purposes. The specimens of drying shrinkage test were opened after one day but, others specimens were demoulded after three days and subjected to air curing under room temperature. As result, the findings from this project are very encouraging towards the use of fly ash